Reef Fish Species Diversity Using Environmental DNA Metabarcoding in Mansinam and Lemon Island Waters, Manokwari Regency - Bayu Pranata; Aradea Bujana Kusuma; Muhamad Ilham Azhar (Jurnal Perikanan Universitas Gadjah Mada, 2022)
Biodiversity has an essential role in the stability of an ecosystem. A high level of biodiversity indicates a more stable and stable ecosystem. The decline in the quality of ecosystems such as coral reefs, seagrass beds, and mangrove forests due to anthropogenic factors and global warming threaten biodiversity. This study aims to determine the diversity of reef fish species using an environmental DNA (eDNA) approach in the waters of the Mansinam and Lemon, Manokwari Regency islands. The analysis results detected 158 individual fish comprising 26 species from 10 families (sequence identity 97-100%). The highest species abundance was found in the Pomacentridae Family. The Pomacentridae family is an ornamental fish species in coral reef ecosystems. In addition, several species from the families Serranidae, Caesionidae, Mullidae, Holocentridae, Balistidae, Scaridae, and Labridae were also detected; fish species from these families are catch targets for fishers with economic value. Assessment of fish species diversity using the Shannon-Wiener method. The diversity of fish species in the waters of the islands of Mansinam and Lemon is in the high category, namely 3.17. High diversity indicates a stable and stable ecosystem condition.